Burocracia de nível de rua e seus impactos na produção de políticas públicas - Rodrigues, Sandra Regina Silva de Oliveira (2023)
This dissertation aims to explore how the profile and performance of street-level bureaucrats impact the implementation of public policies with special emphasis on policies in the area of public health and answer the following question: how does the performance and profile of street-level bureaucrats (BNR) impact the implementation of public policies? The methodology used for this was a systematic literature review (SLR). To reach these articles, the following keywords were used in the research: "street-level bureaucracy, public policies." In light of this action, 16,200 documents were found. The following criteria were used to select them: 1) those that were most cited by other authors; 2) those with an empirical approach; and 3) different authors. Contributions were sought in the literature that elucidate this issue and provide fundamental perspectives on the topic under discussion. It is hypothesized that autonomy and professionalization are relevant elements that enable these bureaucrats to impact and contribute to the refinement and improvement of these policies. In view of this research, an analysis was carried out of the publications found that make up the final theoretical contributions. The results of these studies show that topics such as governance, sustainable development, education policies, street-level bureaucracy, and health policy bring relevant scenarios for the theorization and empirical application of debates in the area. The RSL findings brought to the conclusion that autonomy/discretion and professionalization are really important in the process of implementing, improving and adapting public policies offered to the population. There were also other significant findings beyond the hypotheses presented here. Among them, discretion without supervision and monitoring, at some times and in some situations, can hinder the development of certain public policies. Two other interesting points that appeared in the systematic literature review were: Coping, which can be defined as behavioral efforts that bureaucrats use when interacting with users to tolerate, face or reduce internal or external demands and conflicts that they encounter in everyday life; and the lack of intersectoral implementation processes. It was clear that this is little debated in the literature and that there is no conversation between the implementing sectors about political agendas for implementing a policy. These two findings end up impacting the implementation of public policies and the work of BRNs.